Knowledge of Young Women Regarding the Components of 'My Plate' as a Strategy for Stunting Prevention - Heni Heryani; Lusi Lestari; Suhanda Suhanda (Inspirasi Foundation, 2023)
Introduction: Stunting represents a chronic malnutrition process with significant implications for life productivity. Adolescents, especially young women, wield considerable influence in stunting prevention. Nutritional education stands out as a key strategy in addressing stunting, especially among teenagers. Enhancing nutritional education for adolescents holds promise for shaping their future dietary patterns and behaviors, with knowledge serving as a pivotal catalyst for attitude change. Objective: This research aims to assess the knowledge of young women at SMPN 1 Ciamis regarding the components of 'My Plate' as a preventive measure against stunting. Method: The research methodology employed is descriptive research. The study population comprises young women at SMPN 1 Ciamis, with a sample size of 214 individuals selected through accidental sampling. The questionnaire serves as the primary measuring instrument, and univariate analysis is applied for data analysis. Result: The research findings reveal that the majority of young women exhibit sufficient knowledge, accounting for 91.1%, while the second-largest group demonstrates a lower level of knowledge at 6.1%. Conclusion: There remains a need for increased awareness and socialization regarding the contents of 'My Plate' as a preventative measure against stunting. Collaborative efforts between schools and healthcare providers are encouraged to implement regular programs, including counseling specifically addressing 'My Plate' components and broader initiatives focused on stunting prevention.